PENGARUH LIKUIDITAS, KOMPLEKSITAS OPERASI PERUSAHAAN, STRUKTUR MODAL DAN PROFITABILITAS PERUSAHAAN TERHADAP AUDIT REPORT LAG - Rizki Damir Mustika; Jonnardi (Fakultas Ekonomi Universitas Tarumanagara, 2023)
This study aims to prove and empirically examine the effect of liquidity, company operating complexity, capital structure and profitability on audit report lag in non-bank companies listed on the Indonesia Stock Exchange for the period 2014 – 2018. This study is quantitative with a purposive sampling technique. sampling. Data processing using Multiple Linear Regression through eviews 10 application. Hypothesis testing analysis was carried out partially and simultaneously. The results of this study indicate that: (1) Liquidity with CR (Current Ratio) proxy, Capital Structure with LTDER (Long Term Debt to Equity Ratio) proxy, Profitability with ROA (Return on Assets) proxy has a significant and negative effect on audit report lag in non-bank companies listed on the IDX for the period 2014-2018; (2) The complexity of the Company's Operations with the JTAP proxy (Number of Subsidiaries) has a significant and positive effect on audit report lag in non-bank companies listed on the IDX for the period 2014-2018.